2019
DOI: 10.1039/c9fo00288j
|View full text |Cite
|
Sign up to set email alerts
|

The sources and mechanisms of bioactive ingredients in coffee

Abstract: The sources and mechanism of action of coffee active ingredients are detailed and their joint roles in the prevention of common human diseases are summarized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
85
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 102 publications
0
85
0
1
Order By: Relevance
“…Although studies on coffee ingredients such as chlorogenic acids and caffeine have found their bene cial effects on the health (57), such bene cial effects may be neutralized by other substances added to instant coffee. Third, our MR results re ect the effect of lifetime exposure to coffee intake on cardiometabolic traits (diseases), while experimental studies focus on the effect of short-term exposure, which may be different.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies on coffee ingredients such as chlorogenic acids and caffeine have found their bene cial effects on the health (57), such bene cial effects may be neutralized by other substances added to instant coffee. Third, our MR results re ect the effect of lifetime exposure to coffee intake on cardiometabolic traits (diseases), while experimental studies focus on the effect of short-term exposure, which may be different.…”
Section: Discussionmentioning
confidence: 99%
“…2 Comparisons are to male controls only. 3 Comparisons are to female controls only. 4 Unknown subjects were excluded from calculations.…”
Section: Discussionmentioning
confidence: 99%
“…All of these have many physiological effects, some overlapping with others. When coffee undergoes roasting, amino acids and carbohydrates react through a process called Maillard reactions that produce additional compounds like melanoidins and acrylamide [4,6]. Although little is known, caffeine and polyphenols currently have great neuroprotective properties [14].…”
Section: Review Bioactive Compounds Of Coffee and Their Propertiesmentioning
confidence: 99%
“…Coffee contains more than a thousand compounds, many of which have yet to be found [ 3 ]. Its bioactive components include the most widely known caffeine and others, like chlorogenic acids (CGAs), diterpenes, trigonelline, tryptophan alkaloids, and secondary metabolites that are a product of Maillard reactions called melanoidins [ 4 ]. These have anti-inflammatory, antioxidant, antifibrotic, antimicrobial, and anti-cancer properties that lead to its beneficial role in lowering all-cause mortality and improving endocrine, liver, gastrointestinal, cardiovascular diseases, cancers, and, to which our paper focuses on, neurocognitive function and neurodegenerative diseases [ 5 - 7 ].…”
Section: Introductionmentioning
confidence: 99%